Reading the rabbis : Christian Hebraism in the works of Herbert of Bosham - Visscher, Eva De (Commentaria, 2014)
In Reading the Rabbis Eva De Visscher examines the level of Hebrew scholarship, programme of literal exegesis, and use of Jewish and Christian Hebraist sources in two commentaries on the Psalms by English polymath Herbert of Bosham (c.1120-c.1194).